PERAN IMPULSE BUYING TERHADAP NEGATIVE ONLINE REVIEWS INTENTION MELALUI CONSUMER REGRET (Studi pada konsumen perempuan produk fashion di Shopee) - Rahmatulloh, Tri Ahmad Hilal Rahmatulloh (Seminar Nasional Manajemen, 2025)
This study aims to analyze the influence of Impulse Buying on Negative Online Reviews Intention through Consumer Regret among female consumers of fashion products on Shopee. The phenomenon of increasing impulsive purchases due to massive promotions on e-commerce platforms such as Shopee has led to consumer behavior marked by regret after spontaneous purchases. This regret is divided into two dimensions: Process Regret (regret over the decision-making process) and Outcome Regret (regret over the result of the purchase), both of which can trigger the intention to post negative online reviews. This study uses a quantitative approach with an online survey method. The respondents consisted of 121 female Shopee users who had made impulsive fashion purchases and experienced post purchase disappointment. The sampling technique used was purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4. The results show that Impulse Buying has a positive effect on Process Regret but not on Outcome Regret. Process Regret also positively affects Outcome Regret, while Outcome Regret does not significantly influence Negative Online Reviews Intention. Conversely, Process Regret has a significant influence on Negative Online Reviews Intention. These findings indicate that regret over the decision-making process plays an important role in driving consumers to express their disappointment through online reviews